2018
DOI: 10.1088/1361-6463/aad26a
|View full text |Cite
|
Sign up to set email alerts
|

Carrier lifetime and breakdown phenomena in SiC power device material

Abstract: Recent progress and current understanding of carrier lifetimes and avalanche phenomena in silicon carbide (SiC) are reviewed. The acceptor level of carbon vacancy (VC), called the Z1/2 center, has been identified to be the primary carrier lifetime killer in SiC. The VC defects can be eliminated by the introduction of excess carbon atoms followed by carbon diffusion in the bulk region. The true bulk lifetime after VC elimination was estimated to be approximately 110 µs. The doping dependence of carrier lifetime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 119 publications
1
41
0
Order By: Relevance
“…This bipolar device showed a typical PiN response, turning on at approximately 2.7 V, but with a slightly reduced R ON,SP of 11.9 m.cm 2 . While this is about 4 m.cm 2 lower than the other devices, a lifetime enhancement process [31] would boost conductivity modulation and reduce this further. Despite this, R ON,SP agrees with the already reported values for similar SiC unipolar power diodes [21].…”
Section: Electrical Results Of the Optimized Schottky Devicesmentioning
confidence: 80%
“…This bipolar device showed a typical PiN response, turning on at approximately 2.7 V, but with a slightly reduced R ON,SP of 11.9 m.cm 2 . While this is about 4 m.cm 2 lower than the other devices, a lifetime enhancement process [31] would boost conductivity modulation and reduce this further. Despite this, R ON,SP agrees with the already reported values for similar SiC unipolar power diodes [21].…”
Section: Electrical Results Of the Optimized Schottky Devicesmentioning
confidence: 80%
“… 35 , 36 ) However, the large anisotropy in the electron impact ionization coefficients cannot be explained simply by this relatively small anisotropy in the effective mass near the conduction band bottom and it may originate from the unique structure of the conduction band of SiC. 37 ) Because of the peculiar 〈0001〉 stacking structure of SiC with a four Si-C bilayer period (Fig. 4 (a)), there exist a few minigaps along 〈0001〉 in the k (wavevector)-space inside the conduction band, as shown in Fig.…”
Section: Breakdown Phenomena In Sic Devicesmentioning
confidence: 99%
“…Figure 18 (a) shows the inverse of the carrier lifetime versus carbon vacancy density obtained for very thick and lightly-doped SiC epitaxial layers. 37 , 63 ) The author’s group identified that a carbon vacancy defect creates multiple deep levels called “Z 1/2 center” in the bandgap of SiC by combining deep level transient spectroscopy (DLTS) and photo-excited electron paramagnetic resonance (EPR) measurements on specially-prepared SiC samples. 79 ) As shown in Fig.…”
Section: Progress and Future Challenges Of Ultrahigh-voltage Sic Bipo...mentioning
confidence: 99%
See 1 more Smart Citation
“…However, for electrons, the impact ionization coefficient is assumed to be constant as a function of temperature. This assumption was extracted from calibrations below 425 K. Kimoto et al [31] are currently investigating this phenomenon and believe that this is due to conduction band minigaps (that form due to zone-folding) along the 0001 direction shrinking at high temperature.…”
Section: B Coefficients At Elevated Temperaturesmentioning
confidence: 99%